2006
DOI: 10.1136/hrt.2006.113522
|View full text |Cite
|
Sign up to set email alerts
|

A propensity-matched study of the effect of diabetes on the natural history of heart failure: variations by sex and age

Abstract: Diabetes-associated increases in morbidity and mortality in chronic HF were more pronounced in women, and theses sex-related differences in outcomes were primarily observed in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 31 publications
3
63
0
2
Order By: Relevance
“…Many researchers have used this method in studies of hypertension-related chronic diseases. [33][34][35][36] Statistical analysis. We compared the sample characteristics of patients with hypertension with those of patients without hypertension, before and after the propensity score matching, using the χ 2 test for categorical variables and the Wilcoxon two-sample test for continuous variables.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have used this method in studies of hypertension-related chronic diseases. [33][34][35][36] Statistical analysis. We compared the sample characteristics of patients with hypertension with those of patients without hypertension, before and after the propensity score matching, using the χ 2 test for categorical variables and the Wilcoxon two-sample test for continuous variables.…”
Section: Resultsmentioning
confidence: 99%
“…10,19,20 Obesity is a major risk factor for diabetes mellitus, which is prevalent among heart failure patients. 1,21 A recent subanalysis of a trial from the 1990s, the Digitalis Investigation Group (DIG) study, in a population with chronic heart failure, suggests that obesity confers no survival benefit in heart failure patients with diabetes mellitus. 22 We aimed to evaluate the long-term prognostic impact of BMI according to diabetes mellitus history in a real world community population of chronic systolic heart failure patients followed in a specialized heart failure clinic of a tertiary care academic hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding is consistent with prior analyses of the Danish Investigations of Arrhythmia and Mortality on Dofetilide-HF and the Digitalis Investigation Group trials, which also identified an interaction between diabetes and sex in patients with HF. 4,17 In Danish Investigations of Arrhythmia and Mortality on Dofetilide-HF, diabetes (present in 900 of 5491 patients randomized) was associated with a greater risk of death in women than in men, with relative risks of 1.7 (1.4 to 1.9) and 1. 18,19 and the explanation for this may be multifactorial in origin.…”
Section: Long-term Outcomes: the Interaction Between Diabetes And Sexmentioning
confidence: 99%